1992
DOI: 10.1093/ajh/5.7.459
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Calcium and Insulin Resistance in Elderly Patients With Essential Hypertension

Abstract: We evaluated insulin sensitivity in normotensive (blood pressure, BP, less than 135/85 mm Hg) and hypertensive (BP greater than 160/90 mm Hg) elderly subjects over 65 years old who were stratified as normal weight (body mass index, BMI, less than 27) and obese (BMI greater than 27). Obese hypertensive individuals demonstrated marked hyperinsulinemia (P less than .01) and significantly reduced (P less than .05) submaximally stimulated adipocyte 2-deoxyglucose (2-DOG) uptake (abdominal wall fat biopsy). Normal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 0 publications
3
44
0
3
Order By: Relevance
“…This is supported by previous experimental data [8,9]. Increasing intracellular calcium levels have been shown to decrease the effect of insulin in adipocytes due to the reduced number of glucose transporters (GLUT4) and decreased insulin receptor activity [4,[28][29][30][31]. In an autopsy study performed in consecutive patients, it was shown that parathyroid adenomas and hyperplasia were far more common than the expected prevalence of overt hypercalcaemia [32].…”
Section: Possible Mechanisms For Observed Associationssupporting
confidence: 64%
“…This is supported by previous experimental data [8,9]. Increasing intracellular calcium levels have been shown to decrease the effect of insulin in adipocytes due to the reduced number of glucose transporters (GLUT4) and decreased insulin receptor activity [4,[28][29][30][31]. In an autopsy study performed in consecutive patients, it was shown that parathyroid adenomas and hyperplasia were far more common than the expected prevalence of overt hypercalcaemia [32].…”
Section: Possible Mechanisms For Observed Associationssupporting
confidence: 64%
“…In addition, Ca2+ entry blockade in obese elderly humans resulted in significant increases in peripheral insulin sensitivity (15,16 phosphorylation of Glut4 appeared to be mediated by Ca2+-induced phosphorylation and activation of inhibitor 1, which functions to inhibit phosphoserine phosphatase 1 activity (18). Overall, based on these findings, we predict that the hyperinsulinemia/insulin resistance in the yellow obese mutants causes increased [Ca2+]i in soleus muscle, which induces increased activity of inhibitor 1.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 In the steady state, altered calcium and magnesium levels are present in essential hypertension and in non-insulindependent diabetes mellitus (NIDDM). 2 Elevated basal cytosolic free calcium (Ca i ) levels, as well as defective membrane binding and transport kinetics of calcium, have been identified in platelets, 3 erythrocytes, 4 lymphocytes, 5 and adipocytes 6 of hypertensive subjects, in whom blood pressure levels were closely and directly related to Ca i content. 3,4 In diabetes, even in the absence of overt hypertension, Ca i levels were similarly elevated, 4 and defective calcium handling has been found in all diabetic tissues tested thus far, including cardiac and skeletal muscle, arteries, kidney, liver, erythrocytes, osteoblasts, adipocytes, and platelets.…”
mentioning
confidence: 99%